Métodos de monitoramento de fermentação alcoólica - Santos, Fernanda Correia (Universidade Federal de São Carlos, 2022)
Sugarcane cultivation and ethanol production in Brazil has an active role in the country's economy, sugar since colonization in the 16th century and ethanol since the last century, currently having an important participation in the fuel and food sectors, moving the country's economy. Given the scenario, the present graduation paper presents the main variables of the alcoholic fermentation process and some of the available analysis methodologies used in its monitoring. The variables are divided between physicochemical, which include physical parameters (such as turbidity and temperature) and chemical (such as pH and cell, substrate and ethanol concentrations), and microbiological variables, which concern the yeast responsible for the fermentation and the process’ contamination control by other microorganisms. This paper presents a literature review on alcoholic fermentation and describes the methodologies for obtaining the main process variables. Finally, a critical analysis of current technologies and the industry perspective are presented in order to generate a useful document to help guide the choice of monitoring alcoholic fermentation.
Methods of monitoring alcoholic fermentation
Keywords: Fermentação; Levedura; Etanol; Monitoramento; Fermentation; Yeast; Ethanol; Monitoring; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA